2016
DOI: 10.1002/2015jd024229
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the observed tropospheric BrO background: Importance of multiphase chemistry and implications for ozone, OH, and mercury

Abstract: Aircraft and satellite observations indicate the presence of ppt (ppt ≡ pmol/mol) levels of BrO in the free troposphere with important implications for the tropospheric budgets of ozone, OH, and mercury. We can reproduce these observations with the GEOS-Chem global tropospheric chemistry model by including a broader consideration of multiphase halogen (Br-Cl) chemistry than has been done in the past. Important reactions for regenerating BrO from its nonradical reservoirs include HOBr + Br − /Cl − in both aeros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
315
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(364 citation statements)
references
References 80 publications
44
315
5
Order By: Relevance
“…10, BRCHEM). The underestimation of the absolute OM concentrations by all models besides ECHMERIT is in line with the findings of Schmidt et al (2017), who find that current models strongly underestimate bromine concentrations in this area.…”
Section: North Americasupporting
confidence: 90%
“…10, BRCHEM). The underestimation of the absolute OM concentrations by all models besides ECHMERIT is in line with the findings of Schmidt et al (2017), who find that current models strongly underestimate bromine concentrations in this area.…”
Section: North Americasupporting
confidence: 90%
“…The standard v9-02 model uses Br concentration fields from the GEOS-Chem tropospheric bromine simulation by Parrella et al (2012) and features other model updates relative to Holmes et al (2010), including the gas-particle Hg II equilibrium partitioning described above, a corrected washout algorithm , and improvements to the 2-D surface ocean model (Soerensen et al, 2010). In this work we update the Br concentration fields to a more recent version of GEOS-Chem (Schmidt et al, 2016), as discussed further in Sect. 3.2.…”
Section: General Descriptionmentioning
confidence: 99%
“…Here we further expand and update the chemistry using the mechanism described in Table 1. Br and Cl radical concentrations are taken from a new GEOS-Chem simulation of tropospheric oxidant-aerosol chemistry by Schmidt et al (2016). Unlike Parrella et al (2012), this simulation does not include a bromine radical source from sea salt debromination as recent evidence suggests that BrO concentrations in the marine boundary layer (MBL) are generally sub-ppt (Gómez Martín et al, 2013;Wang et al, 2015).…”
Section: Atmospheric Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Halogens from inorganic (sea-salt) and organic (photodissociation of biogenic compounds) sources, particularly of marine origin, are thought to be important for the tropospheric ozone budget, as they take part in efficient ozone loss catalytic cycles (Read et al, 2008;Saiz-Lopez and von Glasow, 2012;Wang et al, 2015). Studies with single models have shown that this chemistry may have a notable impact on the ozone budget and associated radiative forcing in the troposphere Sarwar et al, 2015;Schmidt et a., 2016;Sherwen et al, 2016aSherwen et al, , 2016b, and the inclusion of tropospheric bromine chemistry has been suggested as a way of partially accounting for the low preindustrial ozone levels suggested by the measurements (Parrella et al, 2012) (although these measurements are uncertain; see TOAR-Observations).…”
Section: Chemistrymentioning
confidence: 99%